Fiscal Policy in Latin America : Lessons and Legacies of the Global Financial Crisis - Celasun, Oya (Staff Discussion Notes; Staff Discussion Notes ;, 2015)
Latin America's bold fiscal policy reaction to the global financial crisis was hailed as a sign that the region had finally overcome its procyclical fiscal past. However, most countries of the region have not yet rebuilt their fiscal space, despite buoyant commodity revenues and relatively strong growth in the aftermath of the crisis. Using the experience of Brazil, Chile, Colombia, Mexico, Peru, and Uruguay, this paper examines the lessons and legacies of the crisis by addressing the following questions, among others: How much did the 2009 fiscal stimulus help growth? What shortcomings were revealed in the fiscal policy frameworks? What institutional reforms are now needed to provide enduring anchors for fiscal policy? How much rebuilding of buffers is needed going forward?